Emerging of a new CD3+CD31HCD184+ tang cell phenothype in Sjögren’s syndrome induced by microencapsulated human umbilical cord matrix-derived multipotent stromal cells - Montanucci, Pia; Bistoni, Onelia; Antonucci, Matteo; Pescara, Teresa; Greco, Alessia; Basta, Giuseppe; Bartoloni, Elena; Gerli, Roberto; Calafiore, Riccardo (Frontiers in Immunology, 2023)
Background: Sjögren’s syndrome (SS) is an autoimmune disease hallmarked by infiltration and destruction of exocrine glands. Currently, there is no therapy that warrants full recovery of the affected tissues. Umbilical cord-derived multipotent stromal cells, microincapsulated in an endotoxin-free alginate gel (CpS-hUCMS), were shown to modulate the inflammatory activity of PBMCs in SS patients in vitro, through release of soluble factors (TGFβ1, IDO1, IL6, PGE2, VEGF). These observations led us to set up the present study, aimed at defining the in vitro effects of CpS-hUCMS on pro- and anti-inflammatory lymphocyte subsets involved in the pathogenesis of SS. Methods and results: Peripheral blood mononuclear cells (PBMCs) upon collection from SS patients and matched healthy donors, were placed in co-culture with CpS-hUCMS for five days. Cellular proliferation and T- (Tang, Treg) and B- (Breg, CD19+) lymphocyte subsets were studied by flow cytometry, while Multiplex, Real-Time PCR, and Western Blotting techniques were employed for the analysis of transcriptome and secretome. IFNγ pre-treated hUCMS were assessed with a viability assay and Western Blotting analysis before co-culture. After five days co-culture, CpS-hUCMS induced multiple effects on PBMCs, with special regard to decrease of lymphocyte proliferation, increase of regulatory B cells and induction of an angiogenic T cell population with high expression of the surface marker CD31, that had never been described before in the literature. Conclusion: We preliminarily showed that CpS-hUCMS can influence multiple pro- and anti-inflammatory pathways that are deranged in SS. In particular, Breg raised and a new Tang phenothype CD3+CD31HCD184+ emerged. These results may considerably expand our knowledge on multipotent stromal cell properties and may open new therapeutic avenues for the management of this disease, by designing ad hoc clinical studies.